A Bacteriological Study of Diabetic Foot Infection in an Urban Tertiary Care Hospital in Dhaka City - Paul, Samir; Barai, Lovely; Jahan, Ashraf; Haq, J Ashraful (Ibrahim Medical College Journal, 2010)
Identification of organisms and effective antibiotic therapy is an important component of treatment of diabetic foot infections. This study was undertaken to determine the organisms associated with diabetic foot infection (DFI) and their antibiotic sensitivity pattern. A total of 75 patients having type 2 diabetes mellitus with Wagner's grade 1-5 foot ulcers attending BIRDEM hospital were included in the study. Specimens were processed for aerobic culture. The bacteriological isolation and antimicrobial sensitivity tests of the isolates were done by standard microbiological methods. Gram negative bacilli were tested for extended spectrum â lactamase (ESBL) production by double disc diffusion method. Culture was positive in 92% of the cases which yielded 135 pathogens. Of the positive culture, 75.3% had multiple organisms. Polymicrobial infection was more in higher grade of foot ulcers. Gram negative organisms were most frequently isolated (80%) bacteria. Pseudomonas (48%) and Proteus sp.(33%) was the most common Gram negative organisms isolated. Staphylococcus aureus was the most commonly isolated gram positive organism (21.3%). ESBL production was noted in 31.5% Gram negative bacilli and methicillin resistance was noted in 43.8% of Staphylococcus aureus. Most of the Gram negative bacilli were resistant to various classes of antibiotics. Imepenem was the most effective agent against Gram negative organisms, while vancomycin was for staphylococcus. The present study has shown that infection with multidrug resistant Gram negative bacilli is the most common cause of DFI in BIRDEM hospital. Ibrahim Med. Coll. J. 2009; 3(2): 50-54 DOI: 10.3329/imcj.v3i2.4216